Analysis of the Critical Discussion of the Statement of Covid-19 on Detik.com Online Media - Wati , Linda; Wardarita, Ratu; Fitriani, Yessi (Jurnal Pendidikan Tambusai, 2021)
Mass media can be used as a means of disseminating information to the public. It cannot be denied that the presence of mass media such as online media can change the way of view, thinking, and reading behavior. More broadly presence of mass media can be used as conduits pemberitaan covid-19 to the public. The reason for conducting this research is to see what critical discourse looks like in online media reporting on detik.com for the period March-May 2020. This research aims to describe critical discourse analysis in online media reporting on detik.com. March-May 2020 period. Based on Teun A. van Dijk's theory, there are twelve editions. The method used in this research is descriptive qualitative with documentation techniques as data collection. Based on the content analysis technique, in this study, the results of the study consisted of macrostructures, superstructures, and microstructures ( micro sematic, micro syntactic, micro stylistic, and micro rhetorical), and hidden ideology.